THE EFFECT OF SERVICE QUALITY ON CUSTOMERS' INTEREST IN SAVING AT BANK BSI (BANK SYARIAH INDONESIA) - Nur Falih Anwar; Indah Cahyani Kartika; Della Wati; Wahyu Hidayat; Henny Saraswati (Department of Sharia Economics, Faculty of Islamic Economics and Business, Universitas Islam Ibrahimy Banyuwangi, Indonesia, 2023)
This research was conducted to evaluate the level of customer satisfaction and intention to save at Bank Syariah Indonesia (BSI). This study uses a quantitative survey method as its methodology. Up to 30 students from the Faculty of Islamic Economics and Business at UIN SMH BANTEN have responded to the survey. Statistical techniques for descriptive and inferential analysis were used to examine the data obtained. The purpose of this research is to understand how customers' interest in saving at Bank Syariah Indonesia (BSI) is influenced by service quality. The research findings show that customers' interest in saving at Bank Syariah Indonesia (BSI) is positively and significantly influenced by service quality. The relationship between customer interest in saving and the quality of services provided is moderate, which implies that the relationship is neither too strong nor too weak but nonetheless substantial. Customer interest in saving at Bank Syariah Indonesia (BSI) is influenced by other variables of 71.5% of these variables, while the remaining 28.5% comes from service quality variables.